2013
DOI: 10.3892/etm.2013.1085
|View full text |Cite
|
Sign up to set email alerts
|

Removal of impacted esophageal foreign bodies with a dual-channel endoscope: 19 cases

Abstract: There have been few reports concerning the endoscopic removal of impacted esophageal foreign bodies from patients. The objective of this study was to evaluate the effectiveness of dual-channel endoscopy in managing foreign-body ingestions in patients. A total of 19 patients with foreign-body ingestions between September 2008 and July 2011 were selected from the Digestive Endoscope Center in Lishui, a typical middle-sized city in China. The patients underwent endoscopy following admission. The impacted foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The first choice of treatment for esophageal foreign body treatment is endoscopy [23]. However, it has been reported that approximately 2% patients experienced esophageal perforation after endoscopic foreign body removal [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first choice of treatment for esophageal foreign body treatment is endoscopy [23]. However, it has been reported that approximately 2% patients experienced esophageal perforation after endoscopic foreign body removal [10].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative dental injury and aspiration of dental prosthesis or tooth are rare complications that could induce catastrophic consequences, such as esophageal perforation and mediastinitis [1234]. Ham et al [5] reported that the incidence of perioperative dental injury was 0.03%.…”
Section: Introductionmentioning
confidence: 99%
“…Most clinical trials comparing RE and FE and have suggested that FB extraction rates of the 2 methods are similar [ 16 , 17 ]. Some reports have recommended that FE be the “first line” approach because it does not require general anesthesia, has shorter operation time, and permits biopsy of the esophageal mucosa [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Endoscopes consist of a flexible tube with diameters ranging from 11 to 30 mm. In addition, a working channel is provided, usually with a diameter in the range of 2.2 to 3.2 mm through which accessories and instruments can be inserted, and in some instances tissue extracted (Wang and Chen 2013). The vision system is fundamental for diagnosis, e.g.…”
Section: Introductionmentioning
confidence: 99%